Deviances from planned purchases: consumer learning history and behavior setting implications for consumer spending - Almeida, Marcos Inácio Severo de; Coelho, Ricardo Limongi França; Porto, Rafael Barreiros; Oliveira, Denise Santos (Review of Business Management, 2020)
Purpose – Consumer spending is an essential measure of performance, and retail decision-makers often strive to understand which factors influence this response variable. We propose that deviations from planned purchases are specific classes of consumer behavior that may explain consumer spending Design/methodology/approach – The research project involved a field experiment in a supermarket where 372 purchases were observed for 13 weeks. Findings – The results show the importance of consumer learning history in predicting consumer groups and the importance of these groups in explaining consumer spending. Originality/value – The results highlight that deviance groups are primarily responsible for spending more or less money on purchases, as well as the importance of consumer learning history and behavioral configuration in explaining behavior. This broadens the scope of the BPM, which often focuses on brand-level results.